Resident perceptions of learning challenges in concussion care education - Kam, Alice; Lam, Tobi; Chang, Irene; Huang, Ryan S; Fernandez, Nicolas; Richardson, Denyse (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2024)
Background: Resident-focused curricula that support competency acquisition in concussion care are currently lacking. We sought to fill this gap by developing and evaluating Spiral Integrated Curricula (SIC) using the cognitive constructivism paradigm and the Utilization-Focused Evaluation (UFE) framework. The evidence-based curricula consisted of academic half-days (AHDs) and clinics for first- and second-year family medicine residents. Our first pilot evaluation had quantitatively demonstrated effectiveness and acceptability but identified ongoing challenges. Here we aimed to better describe how concussion learning is experienced from the learners’ perspective to understand why learning challenges occurred.Methods: A qualitative interpretative cohort study was utilized to explore resident perceptions of concussion learning challenges. Participants completed six monthly longitudinal case logs to reflect on their concussion experience. Semi-structured interviews were conducted.Results: Residents' beliefs and perceptions of their roles influenced their learning organization and approaches. Challenges were related to knowledge gaps in both declarative knowledge and knowledge interconnections. Through reflection, residents identified their concussion competency acquisition gaps, leading to transformative learning.Conclusion: This Spiral Integrated Design created vigorous processes to interrogate “concussion” competency gaps. We discussed resident mindsets and factors that hindered “concussion” learning and potentially unintentional negative impacts on the continuity of patient care. Future studies could explore how to leverage humanistic adaptive expertise, cross-disciplines for curriculum development, and evaluation to overcome the hidden curriculum and to promote integrated education and patient care.